Zeitgeist - how ideas travel : politics, culture, and the public in the age of revolution - Oergel, Maike, 1964- (Culture & conflict ;, 2019)
This book investigates the emergence of the modern concept of zeitgeist--the notion of a pervasive contemporary coherence. It proposes that zeitgeist, as it was discussed by contemporaries of the French Revolution and the Napoleonic Wars in Germany and Britain, contributed to the formation of modern politics and modern societies and captures key aspects of the social process by which ideas are disseminated within societies and across borders--back cover.